Penerapan Convertible Fashion pada Ready to Wear Deluxe Aplikasi Embellishment Resin dan Fabric Painting Inspirasi Bunga Spider Lily - Yulianti, Syifa; Suharno, Suharno; Marlianti, Mira (Jurnal Pendidikan dan Penciptaan Seni, 2025)
The fashion industry innovates with the concept of convertible fashion to meet consumer needs for flexibility and sustainability. This creation research explores the application of this concept to a ready-to-wear deluxe collection through the application of resin embellishment and fabric painting inspired by the Spider Lily flower. The urgency of this research lies in the potential for increasing consumption efficiency, extending the life cycle of clothing, and offering higher functional and aesthetic values. The purpose of this research is to produce an innovative, versatile, and artistic fashion collection by combining convertible fashion with resin embellishment techniques and spider lily-inspired fabric painting. To achieve this goal, this research uses a design thinking approach consisting of five stages, namely: empathize, define, ideate, prototype, and test. This approach was then adapted into six stages by adding the embodiment stage, so it can be called design thinking plus. The result is three sets of clothing that can be combined into nine different looks that offer style flexibility for the wearer.